Bicycling magazine's training techniques for cyclists greater power, faster speed, longer endurance, better skills - Pavelka, Ed (Rodale ; Distributed to the book trade by St. Martin's Press, 1999)
Here's how to achieve optimum cycling performance through proven training techniques from the sport's top experts. Whether you want to ride a competitive century or just want to get the maximum health benefits from cycling, this book will make it happen.